Influence of Pilates training on muscular strength and flexibility in dancers Influência de um programa de treino Pilates na força muscular e flexibilidade de bailarinos - Tânia Patrícia Amorim; Filipa Manuel Sousa; José Augusto Rodrigues dos Santos (Universidade Estadual Paulista (UNESP), 2011)
The purpose of the present study was to assess the effects of a Pilates training program on muscular strength and flexibility in dance students. Fifteen dance students were divided into 2 groups: experimental (n=7) and control (n=8). Both were assessed in beginning and in the end of the study. Muscular strength was assessed measuring the time supported in the technical skills penché and developpé. To asses flexibility, it was measured the angle between limbs in the technical skills arabesque, developpé and cambré. After the first moment of evaluation, the experimental group performed a Mat-Based Pilates Exercise during 11 weeks. The statistic analyses (two-way analysis of variance - ANOVA 2x2) showed significant differences (p ≤ 0,05) in muscular strength and flexibility measurements between groups after the training program. It was concluded that Pilates training has a positive effect on muscular strength and flexibility in dance students. Foi objectivo avaliar o efeito de um programa de treino Pilates na força muscular e flexibilidade de bailarinos estudantes. Quinze bailarinos foram divididos em 2 grupos: experimental (n=7) e controlo (n=8). Ambos foram avaliados no início e final do estudo. A força muscular foi avaliada através do tempo de sustentação nos elementos técnicos penché e developpé. Para avaliar a flexibilidade foi medido o ângulo de amplitude entre os segmentos nos elementos técnicos arabesque, cambré e developpé. Após o 1.º momento de avaliação os bailarinos do grupo experimental participaram num programa de Mat-Based Pilates Exercise durante 11 semanas. A análise estatística (análise de variância para medidas repetidas - ANOVA 2x2) demonstrou diferenças significativas (p ≤ 0,05) entre os grupos no âmbito da força muscular e flexibilidade após o programa de treino. Conclui-se que o Pilates induz alterações positivas ao nível da ça muscular e flexibilidade de bailarinos.